Քաղաքացիական ծառայության կայացման հայեցակարգերը ՀՀ-ում - Վարագյան, Մերի (YSU Journal of International Affairs, 2014)
The article examines the reforms in the civil administration in Armenia and the conceptual model of public service in particular. A comparative analysis of the programs and activities of the Armenian government is made by separately considering the actions planned for each time period, and the expected results. In addition, the article lists the concept of public service and strategic direction of the exercise of its functions.
Keywords: Public administration, Public service, Civil service system, Professional public service, E-government, Informational society, Informational freedom, Anti-corruption strategy